Year of the monkey - Smith, Patti (Bloomsbury Publishing, 2020)
A profound, beautifully realised memoir in which dreams and reality are vividly woven into a tapestry of one transformative year. Following a run of New Year's concerts at San Francisco's legendary Fillmore, Patti Smith finds herself tramping the coast of Santa Cruz, about to embark on a year of solitary wandering. Unfettered by logic or time, she draws us into her private wonderland, with no design yet heeding signs, including a talking sign that looms above her, prodding and sparring like the Cheshire Cat. In February, a surreal lunar year begins, bringing with it unexpected turns, heightened mischief, and inescapable sorrow.
Keywords: Smith, Patti; muusikot; rock; matkat; Yhdysvallat